The Cooke sisters : Education, piety and politics in early modern England. - Allen, Gemma (Politics Culture and Society in Early Modern Britain MUP., 2016)
This book is a study of five remarkable sixteenth-century women. Part of the select group of Tudor women allowed access to a formal education; the Cooke sisters were also well-connected through their marriages to influential Elizabethan politicians. Drawing particularly on the sisters' own writings, this book demonstrates that the sisters' education extended far beyond that normally allowed for sixteenth-century women, challenging the view that women in this period were excluded from using their formal education to practical effect. It reveals that the sisters' learning provided them with oppo.